Adaptive Geometric Constellation Shaping in a Transmission System with a Real-time Optimisation Loop - Jarmolovicius, Mindaugas; Vasylchenkova, Anastasiia; Sillekens, Eric (2023 Optical Fiber Communications Conference and Exhibition (OFC), 2023)
We demonstrate the real-time performance of an adaptive intelligent transceiver, tailoring the constellation shape to the transmission system by iteratively maximising the information throughput, quantified by the GMI.